Eco-Friendly, Multi-Mode Processable Highly Moldable Wood Enabled by the Reconstruction of Hydrogen-Bonding Domain - Yang, Rui; Qi, Linghui; Wu, Xiaoli; Liu, Zhipeng; Bian, Huiyang; Xia, Changlei; Mei, Changtong; Jiang, Shuaicheng; Yao, Meng; Li, Jianzhang (Nano-Micro Letters, 2026)
The production of advanced 3D engineering materials relies on energy-intensive moldable materials such as metals and plastics, making it difficult to cope with the increasingly severe global energy crisis. Wood, as a sustainable material, can be molded through hydrothermal treatment, but the limited plasticity hinders its ability to manufacture precision devices. Herein, the process of hydrogen-bond domain reorganization is used in the manufacture of highly moldable wood to enhance the plasticity of wood and ensure the stability of the cellulose structure. The native hydrogen-bond network in the wood cell wall is disrupted and liberated the cellulose fibril matrix through delignification. Subsequent epoxidized soybean oil acrylate (AESO) plasticization enables significantly enhanced plasticity. Hydrogen-bond domains between fibers are reconstructed through moisture variation. Meanwhile, AESO forms a protective layer on the surface of the fibers, preventing excessive moisture from entering and causing the collapse of the fiber framework. This process allows the material to be shaped into complex 3D geometries, including origami cranes or honeycombs, through low-energy hydrothermal processing. This strategy addresses both dimensional stability challenges and environmental instability associated with wood composite materials and offers an eco-friendly alternative to functionalized structures in aviation and transportation. Highlights: 1 A hydrogen-bond reconstruction strategy creates a moldable wood with greatly improved dimensional stability (≈ 80% lower moisture absorption) and plasticity for precision 3D shaping. 2 We develop a moldable wood that combines high plasticity with exceptional water resistance, enabling the creation of complex, precise 3D structures like mechanical metamaterials. 3 This moldable wood bridges sustainable materials and precision engineering, offering an energy-efficient alternative to synthetic composites in demanding fields like aviation.